Women’s Ritual Art and Intergenerational Knowledge: A Visual Ethnography of Jhuti Practices in Bhadrak District, Odisha - Panda, Taranisen; Mishra, Nirlipta; Ray, Asima; Rahimuddin, Shaik; Pradhan, Bikram; Mohanty, Raj Ballav (UIN Sunan Gunung Djati Bandung, 2025)
Purpose: This study aims to document and analyze the contemporary practice of Jhuti, a women-led ritual art in Bhadrak District, Odisha, by examining its visual motifs, ritual functions, intergenerational transmission, and emerging generational shifts. The research investigates how Jhuti operates as a gendered knowledge system that integrates cosmological symbolism, ecological values, and domestic ritual authority. Methodology: The study employs a two-year visual ethnography (2021–2023) combining participant observation, semi-structured interviews with 97 women practitioners, and photographic documentation across seven administrative blocks. Data were analyzed using thematic coding, motif cataloguing, and cross-generational comparison to identify patterns in ritual participation, material use, symbolic repertoire, and transmission modes. Findings: The research documents twenty-eight distinct Jhuti motifs and reveals a structured symbolic repertoire dominated by Lakshmi paduka (95%), lotus (79%), and conch (71%). Ritual participation remains high during major festivals, particularly Manabasa Gurubara (98%). Jhuti knowledge is transmitted primarily through matrilineal teaching (74%), though reliance on observational learning increases among younger women. Significant generational differences emerge: older women emphasize communal-religious meanings and traditional mud-floor contexts, while younger practitioners favor individual-artistic framings, cement/tile surfaces, and digital modes of learning. The ethnographic vignette demonstrates that embodied, tactile correction remains central to skill transmission and cannot be replaced by digital replication. Implications: The findings highlight urgent needs for heritage preservation strategies that support embodied knowledge transmission, address material-infrastructural constraints in urban settings, and integrate Jhuti into educational and community spaces without detaching it from its ritual cosmology. The study provides evidence to inform policy interventions aligned with UNESCO’s Intangible Cultural Heritage framework, emphasizing sustaining living practices rather than aestheticizing them. Originality and Value: This study offers the first systematic visual ethnography of Jhuti in Bhadrak District, providing an empirically grounded motif catalogue, cross-generational analysis, and detailed documentation of embodied teaching practices. By demonstrating Jhuti’s function as a gendered knowledge system situated at the intersection of devotion, ecology, and domestic authority, the research contributes new conceptual and empirical insights to the fields of ritual studies, women’s art traditions, and intangible heritage preservation.